A model to screen and improve business potential of micro and small enterprises in developing countries: evidence from the Island of Mozambique - Marcos, Ana Margarida (2015)
Programmes supporting micro and small enterprises in developing countries have been showing that capital is not enough to allow business success: survival and growth. Literature does not provide comprehensive and practical tool to support business development in this context, but allowed the collection of forty-nine success variables that were studied in a sample of successful and unsuccessful businesses in the Island of Mozambique to discover what were the key factors affecting those businesses’ performance. Empirical data gave the insights for the development of a model to screen and improve business potential of micro and small enterprises in this context.